Mechanisms of endogenous pain modulation illustrated by placebo analgesia : functional imaging findings - Bingel, U (Schmerz (Berlin, Germany), 2010)
Nociceptive information processing and related pain perception are subject to substantial pro- and antinociceptive modulation. Research on the involved circuitry and the implemented mechanisms is a major focus of contemporary neuroscientific studies in the field of pain and will provide new insights into the prevention and treatment of chronic pain states. Placebo analgesia is a powerful clinical example of the cognitive modulation of pain perception. In placebo analgesia the administration of an inert substance will produce an analgesic effect if the subject is convinced that the substance is a potent analgesic. Recent neuroimaging studies have started to characterize the neural circuitry supporting the placebo analgesic effect. The converging evidence from these studies supports the concept that during placebo analgesia cingulo-frontal regions interact with subcortical structures involved in endogenous antinociception to produce the placebo-induced reduction in pain perception. The subject's report of reduced pain during placebo analgesia coincides with decreased activity in the classic pain areas. This indicates that the altered pain experience during placebo analgesia results from active inhibition of nociceptive input. This cognitively triggered endogenous modulation of pain involves, at least in part, the endogenous opioid system. Most recently, functional magnetic resonance imaging data of the human spinal cord revealed that these mechanisms involve the inhibition of nociceptive processing at the level of the dorsal horn of the spinal cord. Here we discuss recent advances in pain imaging research focusing on cognitively triggered endogenous pain control mechanisms and respective implications for future research strategies.